COMMUNICATION PATTERNS BASED ON SOCIAL MEDIA AS A POLITICAL MARKETING STRATEGY IN INDONESIAN DEMOCRATIC PARTY OF STRUGGLE (Proceedings of the International Conference on Social Sciences, 2018)
This research focus on the pattern of social media-based communication as a determinant of political marketing strategy on the organization of political parties in Indonesia. Research subjects were netizens either as members or administrators of political parties. They were party members and administrators who intensely speak to developments and issues of local election or chatting intensively to actual topics of concern or trending topic using whatApps, line, telegram, facebook applications.  This research method using interpretive / qualitative paradigm which was studied based on netnography study. This method sought to deeply understand the life of the virtual community from the perspective of the perpetrator. The object of the netnographic study was netizens (members and administrators of political parties) with their activities and lives in a virtual world. Data were collected through site observation / broadcast / message service, in depth interview. Data were analyzed using site analysis and thematic analysis based on field data and processed with the help of NVIVO as a qualitative analysis tool. The result of this research that the communication patterns of Indonesian Democratic Party of Struggle (PDI Perjuangan) were formatted in three types: vertical pattern (member-board), horizontal pattern (members and administrators) and diagonal pattern (member-board-member and board-member-board).
Keywords: communication pattern; social media; political marketing strategy; netnography